Optimizing The Use Of Safety Equipment to Prevent Workplace Accidents at KM. Kelud - Siti Humairoh Harliman; Tri Haryanto; Dyah Ratnaningsih; Samsul Huda (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Operational activities on board a ship constitute a work environment with a high risk of workplace accidents. One of the challenges that is still frequently encountered relates to the crew’s suboptimal compliance with safety procedures and the use of personal protective equipment (PPE), resulting in a significant potential for accidents. This study focuses on evaluating the implementation of workplace safety equipment on ships as well as examining crew behavior in support of workplace accident prevention efforts. A qualitative approach was applied in this research, utilizing observation, interviews, and documentation as data collection methods during a 12-month period of sea training aboard the KM. Kelud. Research findings indicate that the occupational safety system has been supported by the availability of safety equipment, standard operating procedures, and the regular conduct of safety meetings. However, its implementation in the field has not been consistent, as it remains influenced by individual awareness levels, established work habits, factors related to workplace comfort, and supervision that has not yet been optimized. Consequently, the use of workplace safety equipment has not been fully effective in reducing workplace accident rates, where human factors remain the most dominant cause. This situation highlights the need to strengthen safety culture through continuous training, improve the effectiveness of supervision, and enforce strict penalties to foster discipline among the ship’s crew.